HAK MASYARAKAT HUKUM ADAT MATTEKO TERHADAP PENGELOLAAN HUTAN ADAT DI KECAMATAN TOMBOLO PAO KABUPATEN GOWA: MATTEKO'S RIGHTS TO THE MANAGEMENT OF TRADITIONAL FORESTS IN TOMBOLO PAO DISTRICT, GOWA DISTRICT - Ridwan, Muhammad; Madiong, Baso; Tira, Andi (Faculty Of Law Bosowa University, 2021)
This research was conducted in Erelembang Village, Buttono Pao District, Gowa Regency and the office of the Alliance for Indigenous Peoples of the Archipelago (AMAN) in South Sulawesi, with the aim of knowing the fulfillment of the requirements for the recognition application for Matteko customary forest in the Kecamatan Buttono Pao and what factors are the obstacles in the application for recognition. Matteko's indigenous peoples' rights to Matteko's customary forest in Tapio Pao District. This research is a normative legal research with a focus on empirical juridical studies. The results of this study indicate that the requirements for the application for recognition of customary forests of the matteko customary law community have been fulfilled and the factors that hinder the recognition of customary law communities are that there are no technical procedures and mechanisms for recognition and respect for indigenous peoples as well as other factors that result in the role of local governments being less optimal in providing protection and recognition of indigenous peoples, the Government has been slow to identify the Matteko indigenous peoples, so that the Matteko indigenous peoples never know their rights and there is no socialization of their customary territories.